Accountability of Budget Management of the Regional Secretariat of Maybrat Regency, West Papua - Meriana Yumami; Sapto Pramono; Ika Devy Pramudiana; Sri Roekminiati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: Accountability of budget management of the Maybrat district secretariat and inhibiting factors of accountability of the budget management of the Maybrat district regional secretariat. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Budget Preparation Procedure of the Maybrat Regency Regional Secretariat is carried out by a budget team that is prepared and implemented for a period of one year. The stages of the budget preparation system start from the guidelines of the SEKDA Work Plan that has been determined using the mixed preparation method (Top Down and Bottom Up). The evaluation process of planning the operational cost budget at the Maybrat Regency Regional Secretariat begins with an evaluation of the budget preparation process schedule guided by Permendagri No. 13 of 2006 and Permendagri No. 59 of 2007. The implementation and administration of the budget at the Maybrat Regency Regional Secretariat is carried out by the Treasurer of the Maybrat Regency Regional Secretariat through recording by the treasurer using general cash books, tax assistant cash books and bank books. The evaluation of the budget financial statements refers to Permendagri No. 113 of 2014 where the Treasurer of the Maybrat Regency Regional Secretariat submits a report on the realization of the implementation of the Budget to the Regional Secretary in the form of a budget realization report. Obstacles Faced in the Accountability of Budget Management of the Maybrat Regency Regional Secretariat include the Low Quality of Human Resources. In addition, the lack of information system facilities related to the financial reporting system is rarely updated or updated.